Brackish-Water Benthic Fauna Under Fluctuating Environmental Conditions: The Role of Eutrophication, Hypoxia, and Global Change - Rousi, Heta; Korpinen, Samuli; Bonsdorff, Erik (Frontiers in Marine Science, 2019)
We studied the spatio-temporal impacts of physical and chemical environmental variables (depth, sediment type, salinity, temperature, oxygen, total phosphorus and total nitrogen) on soft-sediment zoobenthos in the open coastal Gulf of Finland during 2001-2015. The study included 55 sampling-stations covering the east-west gradient of the Finnish coastal zone. The chosen environmental variables significantly influenced the distribution of the species in space and over time. Some zoobenthic taxa formed assemblages with each other, occurring in similar environmental conditions, while Gammarus spp. and Chironomidae clearly differed from other taxa in regards to ecological requirements. We showed the critical influence of oxygen (normoxia, hypoxia, anoxia) on individual species, some better adapted to low oxygen conditions (e.g. Chironomidae) than others (e.g. Monoporeia affinis). The nutrient concentrations in the surface sediment also significantly affected the benthic assemblage patterns. The number of species in space and time increased with increasing oxygen concentrations. This study clearly shows that in order to maintain healthy marine communities, it is essential to counteract excess nutrient inputs and their indirect effects on sufficient O2 conditions for the benthic habitats.